SPECIAL EFFECTS OF CERTAIN TYPES OF WEAPONS ON MILITARY PERSONNEL IN COMBAT ZONES - Kalnysh, V.V.; Serheta, I.V.; Pashkovskiy, S.M.; Tymchyshyn, T.P.; Anhelska, V.Yu. (World of Medicine and Biology, 2025)
Based on the complex of sensations resulting from combat stress factors associated with the use of different types of weapons, three age groups were identified among the military personnel (Group 1: ≈30 years; Groups 2 and 3: ≈41 years). The study demonstrated that age has a significant effect on the nature of sensations caused by combat stress factors: younger respondents exhibited higher sensitivity to most of these factors. The most stress-inducing factors were identified as shelling involving unmanned aerial vehicles, guided aerial bombs, and attacks from tanks and artillery. Military personnel of older age groups tended to exhibit lower levels of sensitivity, which may be explained by accumulated combat experience, habituation to danger, or a decrease in the body’s functional reserves. The findings also highlight the physiological and psychological effects associated with exposure to specific types of weapons.